Supply–demand strategies for near-term climate benefits from hydrogen in the United States - Youyi Xu; Wei Peng; Yuan Yao (Proceedings of the National Academy of Sciences, 2025)
Hydrogen (H 2 ) is a promising energy carrier for decarbonization. However, the greenhouse gas (GHG) mitigation potential of the H 2 supply and its adoption across various demand sectors in the US remains unclear. Here, we couple prospective life cycle assessment with a process-based integrated assessment model to evaluate the GHG mitigation of H 2 from supply and demand perspectives. Our results show the critical role of H 2 production mix in determining supply-side GHG mitigation potential. Without national carbon pricing or large-scale electrolysis in the near future, biomass-based H 2 (Bio-H 2 ) emerges as a critical transitional clean H 2 production technology. Bio-H 2 reduces the life cycle GHG emission intensity of the H 2 supply mix by 1.8 to 5.5 kg CO 2 kg −1 H 2 , resulting in a national reduction of 606 to 1,706 Mt CO 2 e from 2025 to 2050. This represents 1.6 to 2 times greater mitigation potential compared to scenarios without Bio-H 2 . On the demand side, we identify a misalignment: industrial sectors with high mitigation intensity (e.g., iron and steel, 147 Mt CO 2 e EJ −1 ) receive limited H 2 deployment (0.8 EJ), while the transportation sector accounts for 75% of H 2 use (e.g., passenger and light-duty vehicles, 10 EJ) despite their lower mitigation intensities (54 Mt CO 2 e EJ −1 ). While economy-wide climate policies (e.g., carbon prices) could direct more industrial H 2 usages, implementing these policies is challenging; sector-specific strategies can be more practical. Our results highlight the importance of near-term support for Bio-H 2 and sector-specific demand strategies to enhance the climate effectiveness of US H 2 deployment.